2019
DOI: 10.1007/s10096-019-03531-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of fosfomycin resistance among ESBL-producing Escherichia coli isolates in the community, Switzerland

Abstract: Our aim was to evaluate the prevalence of fosfomycin-resistant strains among ESBL-producing Escherichia coli isolates recovered from community patients in Switzerland. A total of 1225 ESBL-producing E. coli isolates were collected between 2012 and 2013 from a private and community laboratory. Fosfomycin resistance was assessed by using the novel rapid fosfomycin/E. coli NP test and agar dilution method. Resistant isolates were further investigated for acquired resistance genes fosA1-7 by PCR and sequencing. Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 21 publications
4
36
0
Order By: Relevance
“…We used standard PCR conditions to amplify the β-lactamase gene bla CMY , encoding plasmid-mediated cephalosporinases [ 22 ]. Fosfomycin resistance due to a transferable glutathione- S -transferase FosA-like enzyme was searched by using the phosphonoformate test [ 23 ] after which plasmid-borne fosfomycin resistance determinants were identified by PCR followed by sequencing [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…We used standard PCR conditions to amplify the β-lactamase gene bla CMY , encoding plasmid-mediated cephalosporinases [ 22 ]. Fosfomycin resistance due to a transferable glutathione- S -transferase FosA-like enzyme was searched by using the phosphonoformate test [ 23 ] after which plasmid-borne fosfomycin resistance determinants were identified by PCR followed by sequencing [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial strains and plasmids. E. coli isolate 376 was isolated from urine in the context of screening 1,225 ESBL-producing E. coli isolates from a Swiss collection obtained from 2012 and 2013 (20). The list of strains and plasmids used in the study is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The determination of the plasmid incompatibility group was confirmed by PCR-based replicon typing (PBRT) (30). Conjugation experiments were performed using E. coli strain 376 and azide-resistant strain E. coli J53 as donor and recipient strains, respectively, as described previously (20). Both donor and recipient strains were cultured in exponential phase and then mixed on solid Luria Broth agar using filters at a 1:10 donor/recipient ratio.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently performed a screening of fosfomycin resistance among a collection of ESBL-producing E. coli from Switzerland recovered in 2012 (17). Hence, we identified a fosfomycin-resistant isolate harboring a novel fos gene coding for a putative glutathione S-transferase located on a conjugative plasmid.…”
mentioning
confidence: 99%